PENGEMBANGAN PERMAINAN TRADISIONAL CONGKLAK PEMBELAJARAN MATEMATIKA MATERI PERKALIAN KELAS II SD NEGERI 76 LUBUKLINGGAU - Kusmita Sari, Tazu (LP3MKIL, 2022)
This study aims to develop a traditional game media congklak in learning mathematics multiplication material that meets the valid and practical criteria. The research method is Research and Development which refers to the 4D development model. The population was taken by all second grade students of the 76 Lubuklinggau State Elementary School and the sample of this study amounted to 6 students. Data collection techniques were carried out using interview techniques, documentation and data analysis techniques in the form of product assessment questionnaires to assess aspects of validity, student response questionnaires to assess practical aspects. The results of the research on the validity of the analysis of linguists obtained a value of 0.77, the analysis of media experts obtained a value of 0.92 and material analysis obtained a value of 0.90. The results of practicality research from small group analysis get a score of 95% and the results of the practicality analysis of teachers get a score of 91%. It can be concluded that the analysis results from the expert validation of the Congklak traditional game media got a final score with an average of 0.86 and was adjusted to the validity interpretation table with a high category for the practicality value of the Congklak traditional game media which was adjusted to the practicality table into the very practical category